Аналіз інноваційних підходів до податкового обліку в умовах цифровізації економіки - Лоскоріх Габріелла; Loszkorih Gabriella; Gabriella Loskorikh; Шебештень Едіна; Sebestyén Edina; Edina Shebestyen; Пономарьова Наталія; Nataliya Ponomaryova (Львівський університет бізнесу та права, 2025)
Резюме. У статті розглянуто сучасний стан цифровізації податкового обліку та основні інноваційні підходи до його розвитку. Досліджено роль цифрових технологій, таких як електронний документообіг, блокчейн, штучний інтелект та автоматизовані системи контролю, у підвищенні ефективності податкового адміністрування. Визначено основні переваги цифровізації, серед яких зменшення адміністративних витрат, боротьба з корупцією, підвищення податкових надходжень та покращення взаємодії між платниками податків і органами контролю. Окреслено основні виклики, що перешкоджають упровадженню цифрових технологій у податковий облік, зокрема необхідність удосконалення інформаційної інфраструктури, підвищення цифрової грамотності та захист кібербезпеки. У висновку окреслено перспективні напрями розвитку цифрового податкового обліку, зокрема інтеграцію штучного інтелекту, аналітичних платформ та адаптацію законодавчої бази до нових технологічних реалій.

Abstract. The article examines the current state of tax accounting digitalization and the main innovative approaches to its development. The key directions of digital transformation of tax processes, which contribute to the automation of tax data collection, analysis, and storage, are outlined. The role of digital technologies, including electronic document management, blockchain technologies, artificial intelligence, and automated control systems, in enhancing the efficiency of tax administration is explored. The advantages of tax accounting digitalization are characterized, including the reduction of administrative burdens, acceleration of tax reporting processes, increased transparency, and reduced corruption risks. The implementation of digital technologies improves interaction between taxpayers and regulatory authorities while ensuring higher compliance with tax legislation. The integration of electronic reporting systems enables businesses to streamline tax documentation, minimizing human errors and expediting tax filing procedures. Blockchain technology enhances data security and ensures the immutability of tax records, reducing opportunities for fraud and tax evasion. The main challenges of tax accounting digitalization are identified, such as the need for modernization of information infrastructure, improvement of digital literacy among taxpayers and government officials, and ensuring cybersecurity to protect confidential tax information. The transition to digital tax administration requires significant financial investment and comprehensive reforms to align regulatory frameworks with technological advancements. Addressing these challenges is crucial for achieving a seamless and efficient tax ecosystem that benefits both taxpayers and government institutions. In conclusion, the article outlines the promising directions for the development of digital tax accounting, particularly the expanded use of artificial intelligence, analytical platforms for tax risk forecasting, improvement of automated control methods, and adaptation of the legal framework to new technological realities. The ongoing evolution of digital tax systems will facilitate more accurate tax assessments, improve compliance monitoring, and enhance overall economic governance. The integration of cloud-based tax solutions and data analytics will further contribute to optimizing tax collection processes and strengthening financial oversight at both national and international levels.
Analysis of innovative approaches to tax accounting in the conditions of digitalization of the economy
Весь випуск: https://nzlubp.org.ua/index.php/journal/issue/view/28
Keywords: податковий облік; цифровізація; електронний документообіг; автоматизація; штучний інтелект; tax accounting; digitalization; electronic document management; automation; artificial intelligence